EXpert consensus On Diaphragm UltraSonography in the critically ill (EXODUS): a Delphi consensus statement on the measurement of diaphragm ultrasound-derived parameters in a critical care setting - Haaksma, Mark E.; Smit, Jasper M.; Boussuges, Alain; Demoule, Alexandre; Dres, Martin; Ferrari, Giovanni; Formenti, Paolo; Goligher, Ewan C.; Heunks, Leo; Lim, Endry H. T.; Mokkink, Lidwine B.; Soilemezi, Eleni; et al. (Critical care (London, England), 2022)
Background Diaphragm ultrasonography is rapidly evolving in both critical care and research. Nevertheless, methodologically robust guidelines on its methodology and acquiring expertise do not, or only partially, exist. Therefore, we set out to provide consensus-based statements towards a universal measurement protocol for diaphragm ultrasonography and establish key areas for research. Methods To formulate a robust expert consensus statement, between November 2020 and May 2021, a two-round, anonymous and online survey-based Delphi study among experts in the field was performed. Based on the literature review, the following domains were chosen: “Anatomy and physiology”, “Transducer Settings”, “Ventilator Impact”, “Learning and expertise”, “Daily practice” and “Future directions”. Agreement of ≥ 68% (≥ 10 panelists) was needed to reach consensus on a question. Results Of 18 panelists invited, 14 agreed to participate in the survey. After two rounds, the survey included 117 questions of which 42 questions were designed to collect arguments and opinions and 75 questions aimed at reaching consensus. Of these, 46 (61%) consensus was reached. In both rounds, the response rate was 100%. Among others, there was agreement on measuring thickness between the pleura and peritoneum, using > 10% decrease in thickness as cut-off for atrophy and using 40 examinations as minimum training to use diaphragm ultrasonography in clinical practice. In addition, key areas for research were established. Conclusion This expert consensus statement presents the first set of consensus-based statements on diaphragm ultrasonography methodology. They serve to ensure high-quality and homogenous measurements in daily clinical practice and in research. In addition, important gaps in current knowledge and thereby key areas for research are established. Trial registration The study was pre-registered on the Open Science Framework with registration digital object identifier https://doi.org/10.17605/OSF.IO/HM8UG .